Consensus guidelines for enhanced recovery after gastrectomy. Issue 10 (21st July 2014) - Mortensen, K; Nilsson, M; Slim, K; Schäfer, M; Mariette, C; Braga, M; Carli, F; Demartines, N; Griffin, S M; Lassen, K; ,
Abstract: Background: Application of evidence-based perioperative care protocols reduces complication rates, accelerates recovery and shortens hospital stay. Presently, there are no comprehensive guidelines for perioperative care for gastrectomy. Methods: An international working group within the Enhanced Recovery After Surgery (ERAS®) Society assembled an evidence-based comprehensive framework for optimal perioperative care for patients undergoing gastrectomy. Data were retrieved from standard databases and personal archives. Evidence and recommendations were classified according to the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) system and were discussed until consensus was reached within the group. The quality of evidence was rated 'high', 'moderate', 'low' or 'very low'. Recommendations were graded as 'strong' or 'weak'. Results: The available evidence has been summarized and recommendations are given for 25 items, eight of which contain procedure-specific evidence. The quality of evidence varies substantially and further research is needed for many issues to improve the strength of evidence and grade of recommendations. Conclusion: The present evidence-based framework provides comprehensive advice on optimal perioperative care for the patient undergoing gastrectomy and facilitates multi-institutional prospective cohort registries and adequately powered randomized trials for further research. Abstract : Best available evidence for these patients